Financial Crisis and Impairment Recognition in Non-Financial Assets - Gaio, Cristina; Gonçalves, Tiago; Pereira, Anabela (Review of Business Management, 2021)
Purpose – To analyse the impact of the financial crisis on the recognition of non-financial asset impairments in European listed companies. Theoretical framework – The study explores the impact of the theory of measuring the economic value of non-financial assets on managers’ decisions to recognize impairments, especially in the context of an economic crisis. Design/methodology/approach – Logit and ordinary least squares models were estimated to analyse the probability of recognition and the amount of impairment recognized, respectively, over a 10-year period. Findings – The results show that European companies recognized less impairments during the crisis, including companies in countries that have used external financial aid, suggesting that managers may use impairment recognition as a way of practicing earnings management. Research Practical & Social implications – The results are of interest to several stakeholders, namely: creditors, investors, financial market regulators, entities that prepare and oversee the application of accounting and auditing standards, and ultimately European leaders in terms of structural reforms and investor protection laws. Originality/value – The study contributes to the literature that analyses the impact of the financial crisis on the recognition of impairments in non-financial assets and, in particular, in the context of greater financial fragility. It also contributes to the literature on the use of discretion in the recognition of impairments and earnings management practices. Moreover, it adds to the theoretical debate regarding the principles of measurement in the context of impairment, and how this may affect assessments of the economic values of non-financial assets. Keywords – financial crisis; European listed companies; non-financial asset impairments; earnings management.